Dyfuzja od Źródła Punktowego w Kanale Otwartym - W. Czernuszenko (Engineering Transactions, 1974)
The paper contains the analysis of the process of mass transport of the indicator flowing out from the point source placed in an open channel. The flow is turbulent and the channel is wide enough to disregard the influence of its walls on the transport process. Parabolic equation of turbulent diffusion is used and solved under the assumption of totaI reflection of the diffusing mass at the free water surface. The solution is discussed for various positions of the point source, the influence of free water surface on the transport process being considered. The results are verified by means of a physical model  a concrete channel with flowing water. The diffusing mass was represented by the water solution of B rhodamine introduced into the flow at a rate corresponding to the average velocity of water. Its concentration was measured by fluorimetric methods. Results of the investigations may found an application in various practical problems connected with water pollution.